Pengaruh Hypnoterapi Terhadap Penurunan Skala Nyeri Pada Lansia Penderita Gout Arthritis Di Posyandu Lansia Puskesmas Pademawu Pamekasan - Mohammad shidiq suryadi (Wiraraja Medika : Jurnal Kesehatan, 2020)
ABSTRACT Gout arthritis often causes elderly sufferers to complain that there is a decline in daily activities which results in decreased musculoskeletal function due to pain as a result of gout arthritis. Besides pain, gouty arthritis also causes the elderly to be anxious to actively carry out daily activities due to the pain that often arises. (Smeltzer & Bare, 2009). This study aims to determine whether there is an effect of hypnotherapy on pain scale reduction in gout arthritis in elderly Posyandu Puskesmas Pademawu Pamekasan. The design used in this study uses Quasy-Experimental with a pre post test control group design approach. The number of samples in this study were all Gout Arthritis patients in the Posyandu Elderly Pademawu Public Health Center Pamekasan District as many as 47 people 17 treatment groups and 17 control groups using Non-Probability Sampling techniques with Purposive Sampling. while the data analysis is done by paired t test and independent t test with a 95% confidence interval or with a value of α = 0.05. Statistical test results obtained Sig (2-Tailed) = 0,000. It means that there is an influence of hypnotherapy on the decrease in pain scale in gout arthritis in Posyandu Elderly Pademawu Puskesmas, Pamekasan. This research is expected to be an additional information and knowledge in the field of nursing about non-pharmacological pain management by using hypnotherapy to reduce pain scale. Key word: Hypnotherapy, Pain Scale